Risk of breast cancer risk factors in women aged 20 to 65 years (Jóvenes en la Ciencia, 2024)
Breast cancer is one of the three main types of cancer in Mexico, a percentage of all deaths from breast cancer are due to alcohol consumption, overweight, obesity, and lack of physical activity. In Mexico it is the second most common cause of cancer in women and in some states of the republic it is the first cause of death from cancer in women, surpassing cervical carcinoma. Objective: To evaluate the level of risk of breast cancer in women aged 20 to 65. years. A descriptive and cross-sectional study was carried out through a survey of women between 20 and 65 years old during the period January-July 2024. In which informed consent was previously granted to subsequently carry out the survey. In the research it was found that, of the 17 people surveyed, 12 are in a menopausal state, representing 71% of the total sample, while 5 people are not in a menopausal state, representing 29%. % of the total sample. Of the 17 people surveyed, 10 have stopped menstruating, representing 59% of the total population, while 7 people still continue menstruating, representing 41% of the total population. dictates that, Likewise, of the 17 people surveyed, 15 of them do not receive or have received replacement therapy in their lives, representing 88% of the sample, while 2 people have received replacement therapy, representing, in turn, 12% of the sample. In turn, of the 17 people surveyed, 10 have had children and at the same time have breastfed them, representing 59% of the sample. Meanwhile, 41% have not breastfed, of which 3 have not had children and 4 have had, but have not provided breastfeeding. Finally, of the 17 people surveyed, 10 of them have a history of breast cancer in their family, representing 59% of the sample, while 41%, represented by 7 women, affirm that there are no cases of breast or breast cancer. history of it in his family. These results suggest that the female population has risk factors that may lead to a higher risk of developing CA.